Proceedings of the 21st ACM International Conference on Information and Knowledge Management 2012
DOI: 10.1145/2396761.2398492
|View full text |Cite
|
Sign up to set email alerts
|

Time-aware topic recommendation based on micro-blogs

Abstract: Topic recommendation can help users deal with the information overload issue in micro-blogging communities. This paper proposes to use the implicit information network formed by the multiple relationships among users, topics and micro-blogs, and the temporal information of micro-blogs to find semantically and temporally relevant topics of each topic, and to profile users' timedrifting topic interests. The Content based, Nearest Neighborhood based and Matrix Factorization models are used to make personalized re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…The documents in qi.R1 are sorted in descending order of their arrival times. In particular, for each document di we store: (1) Document id; (2) Text relevance between qi and di; (3) Accumulated similarities of di, computed by Equation 24, is the sum of similarities between di and the documents in qi.R with arrival times earlier than di.…”
Section: Query Results Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…The documents in qi.R1 are sorted in descending order of their arrival times. In particular, for each document di we store: (1) Document id; (2) Text relevance between qi and di; (3) Accumulated similarities of di, computed by Equation 24, is the sum of similarities between di and the documents in qi.R with arrival times earlier than di.…”
Section: Query Results Indexmentioning
confidence: 99%
“…It is introduced in [23] and is applied (e.g., [2,24,32]) as the measurement of recency for stream data. Based on the experimental studies [14], the exponential decay function has been shown to be effective in blending the recency and text relevancy of documents.…”
Section: Problem Statementmentioning
confidence: 99%
“…Furthermore, our work focuses on a secondary item unit -version updates, which is a separate entity from primary item (i.e., the app). Liang et al [14] proposed a method to capture the temporal dynamics of relevant topics in micro-blogs (e.g., Twitter) where a topic centers around a certain theme such as the U.S. presidential election or Kate Middleton's baby which, in the micro-blogging community, may change quickly with time. Our work differs from theirs as the "items" in their system are the topics, which is an indefinite discourse.…”
Section: Time-sensitive Recommendationmentioning
confidence: 99%
“…Many techniques like tensor factorization [22,23,26] and graph model [5,7] have been proposed and applied to different social tagging systems like Flickr and Delicious. For Twitter, both user-based recommendation [4,14] and tweet-based recommendation have been proposed for hashtag recommendation [13,16,25,32]. Next, we briefly survey tweet-based recommendation for being more relevant to our work.…”
Section: Hashtags In Twittermentioning
confidence: 99%